Sugarbeet tolerance when dimethenamid-P follows soil-applied ethofumesate and S-metolachlor. (June 2019) - Peters, Thomas J.; Lueck, Andrew B.; Carlson, Aaron L.
Abstract: Sugarbeet growers only recently have combined ethofumesate, S -metolachlor, and dimethenamid-P in a weed control system for waterhemp control. Sugarbeet plant density, visible stature reduction, root yield, percent sucrose content, and recoverable sucrose were measured in field experiments at five environments between 2014 and 2016. Sugarbeet stand density and stature reduction occurred in some but not all environments. Stand density was reduced with PRE application of S -metolachlor at 1.60 kg ai ha –1 and S -metolachlor at 0.80 kg ha –1 + ethofumesate at 1.68 kg ai ha –1 alone or followed by POST applications of dimethenamid-P at 0.95 kg ai ha –1 . Sugarbeet visible stature was reduced when dimethenamid-P followed PRE treatments. Stature reduction was greatest with ethofumesate at 1.68 or 4.37 kg ha –1 PRE and S -metolachlor at 0.80 kg ha –1 + ethofumesate at 1.68 kg ha –1 PRE followed by dimethenamid-P at 0.95 kg ha –1 POST. Stature reduction ranged from 0 to 32% 10 d after treatment (DAT), but sugarbeet recovered quickly and visible injury was negligible 23 DAT. Although root yield and recoverable sucrose were similar across herbicide treatments and environments, we caution against the use of S -metolachlor at 0.80 kg ha –1 + ethofumesate at 1.68 kg ai ha –1 PRE followed by dimethenamid-P at 0.95 kg ha –1 in sugarbeet.